Linezolid Is Associated with Serotonin Syndrome in a Patient Receiving Amitriptyline, and Fentanyl: A Case Report and Review of the Literature - Lampros Samartzis; Paraskevi Savvari; Sofoklis Kontogiannis; Stavros Dimopoulos (Case Reports in Psychiatry)
We report a unique case of an adverse interaction between the oxazolidinone antibiotic linezolid, the tricyclic antidepressant amitriptyline and the opioid analgesic fentanyl in a 68-year-old woman with advanced ischemic peripheral arterial disease and sepsis, under empirical antibiotic treatment. We also summarize the current relevant literature as identified via PubMed, EMBASE, and PsycINFO as well as reference sections of selected articles.